Demon Dentist - Williams, David (USA, 2013)
Darkness had come to the town. Strange things were happening in the dead of night. Children would put a tooth under their pillow for the tooth fairy, but in the morning they would wake up to find... A dead slug; a live spider; hundreds of earwigs creeping and crawling beneath their pillow...
Keywords: Adventure; Humorous; Juvenile Fiction